Essential Readings in Light Metals, Volume 4, Electrode Technology for Aluminum Production - Tomsett, Alan; Johnson, John (The Minerals, Metals & Materials Series, 2016)
This compilation is the most comprehensive historical collection of papers written on primary aluminum science and technology. It is a definitive reference in the field of aluminum production and related light metals technologies and contains a strong mix of materials science and practical, applied technology. Written for materials scientists and engineers, metallurgists, mechanical engineers, aerospace and automobile engineers, electrical and electronics engineers, this volume is a valuable resource for the global aluminum and light metals industries.